Chemical Face Peeling - Langsdon, Phillip R.; Shires, Courtney B. (Facial Plastic Surgery, 2012)
Chemexfoliation is an excellent method to reduce facial rhytids. For 25 years, we have used the traditional formula as described by T. J. Baker but with a moist healing technique rather than a tape mask. We have found the peel to be inexpensive and easy to perform, with results that are excellent and consistent, with minimal side effects.
Keywords: chemical peel; phenol; rhytids; chemexfoliation